2015
DOI: 10.1111/bjh.13870
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical features and prognostic factors in solitary plasmacytoma

Abstract: SummaryThis study aimed to review the clinical features and outcome of 53 patients with solitary plasmacytoma managed at our Institution between 1976 and 2012. Thirty-five patients had bone solitary plasmacytoma and 18 extramedullary solitary plasmacytoma. Tumour sizes were larger in patients with bone involvement (P = 0Á003). Treatment consisted of local radiotherapy (n = 26), radiotherapy + chemotherapy (n = 15), surgery (n = 4) and chemotherapy (n = 8); the local control rate was 94Á3%. Progression to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
5
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 41 publications
(75 reference statements)
7
65
5
6
Order By: Relevance
“…This was not in accordance with results reported by Jawad et al and Knobel et al [5, 10]. However, a recent retrospective study by Finsinger et al, who evaluated 53 patients, found there was a significant difference in progression-free survival (PFS) between patients who received RT and those who received other treatment modalities [24]. Despite the excellent local control, in our study, at least 70% of patients who received RT progressed to myeloma.…”
Section: Discussionmentioning
confidence: 74%
“…This was not in accordance with results reported by Jawad et al and Knobel et al [5, 10]. However, a recent retrospective study by Finsinger et al, who evaluated 53 patients, found there was a significant difference in progression-free survival (PFS) between patients who received RT and those who received other treatment modalities [24]. Despite the excellent local control, in our study, at least 70% of patients who received RT progressed to myeloma.…”
Section: Discussionmentioning
confidence: 74%
“…Solitary extramedullary plasmacytoma (SEP) is a rare tumor accounting for only 3–5% of all plasma cell neoplasms [6]. It is defined as either primary, when it occurs as isolated mass, or secondary, when it is associated with generalized multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Regional recurrence and distant metastasis may develop in 22% of patients and 15% will develop generalized myeloma [8]. SEP prognosis is considered good with a median survival of approximately 10 years [6]. …”
Section: Discussionmentioning
confidence: 99%
“…It accounts for 3 to 5% of all plasma cell neoplasms [1]. Almost 85% of EMPs involve the head and neck mucosa, especially in the upper respiratory tract [2]. Gastrointestinal, lung, bladder, and testis involvement have also been reported.…”
Section: Introductionmentioning
confidence: 99%